Oral Epigallocatechin Gallate Decreases Bioavailability Of Nadolol Via Modulation Of Ileal And Hepatic Oatp1a5, Mdr1a And Oct1 Mrna Levels In Spontaneously Hypertensive Rats - Tan, Hong Jie (2022)
Concurrent use of epigallocatechin-3-gallate (EGCG) and medication may induce herb-drug interactions, which lead to therapeutic failure or drug toxicity if leave negligence. It has been reported that EGCG reduces bioavailability of plasma nadolol in normotensive models. Nevertheless, evidence on the effects of EGCG on hypertensive model, and the possible underlying mechanism have not been elucidated. This study aims (i) to investigate the effects of EGCG on bioavailability of nadolol (maximum plasma concentration, time required to reach maximum concentration in plasma, area under the time-plasma concentration curve, plasma half-life and total clearance) and subsequently its impact on blood pressure control; and (ii) to identify transcriptional regulatory roles of EGCG on the nadolol intestinal and hepatic drug-transporters in spontaneously hypertensive rats. Male SHR were pre-treated with EGCG (10 mg/kg body weight, i.g.), once daily dose for consecutively 13 days. At day-14, a single dose of nadolol (10 mg/kg body weight) was given to the rats 30 minutes after the last dose of EGCG administration. Systolic blood pressure (SBP) was measured at 6-h and 22-h post-nadolol administration. Plasma and urinary excreted nadolol concentrations were quantified via high performance liquid chromatography, and the pharmacokinetic parameters were analysed by using non-compartmental analysis. Hepatic and ileal Oatp1a5, Mdrla, and Oct1 mRNA expressions were determined by real-time PCR. SBP of SHR pre-treated with EGCG and received nadolol was significantly higher than those which were not pre-treated with EGCG but received nadolol. Pre-treatment of EGCG resulted in a marked reduction of plasma nadolol maximum concentration (Cmax) and area under the time-plasma concentration curve (AUC) by 53% and 51% compared to its control. The 14-day treatment with oral EGCG led to a significant downregulation of mRNA levels of ileal Oatp1a5, Mdr1a, and Oct1 genes by 4.03-, 8.01- and 4.03-fold; and hepatic Mdr1a, and Oct1 genes by 2.61- and 2.66-fold. These data concluded that exposure to EGCG reduces bioavailability of nadolol and caused uncontrolled raised blood pressure with increased risks of cardiovascular events. Our data suggest that the reduced bioavailability of nadolol associates with the downregulation of ileal Oatp1a5 and Oct1 mRNA levels that subsequently lead to poor absorption of nadolol to the systemic circulation.